2017
DOI: 10.1002/ejoc.201700692
|View full text |Cite
|
Sign up to set email alerts
|

The Ambivalent Nature of Halogenated Tropone Derivatives: Dihalocycloheptatriene vs. Halotropylium Halide

Abstract: Although dichlorocycloheptatriene and dibromocycloheptatriene have been known for a long time, their exact structure remained uncertain so far. In this computational and crystallographic study, we elucidate the nature of these compounds in solution and in the solid state. In the latter case, both compounds exist as halotropylium halides, which also feature Br–Br halogen bonds in the case of bromotropylium bromide. In solution, there is a highly dynamic equilibrium involving both the ionic halotropylium halide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The seven-membered ring is close to being perfectly planar, with no C-C-C-C torsion angle deviating from 0/180 by more than 3 , thus supporting the idea of an aromatic tropylium system. The average of the C-C bond length [1.393 (3) Å ] is close to the values reported for halogen-substituted and unsubstituted tropylium ions (Jandl et al, 2017). However, in contrast to halotropylium ions, the C-C bond lengths of the hydroxytropylium ion show an alternation between the longer C1-C2, C3-C4, C5-C6 and C1-C7 bonds, and the shorter C2-C3, C4-C5 and C6-C7 bonds (Table 2) Computer programs: APEX2 (Bruker, 2013), SAINT (Bruker, 2012), SHELXS97 (Sheldrick, 2008), SHELXL2014 (Sheldrick, 2015), ShelXle (Hü bschle et al, 2011), PLATON (Spek, 2009), Mercury (Macrae et al, 2006), enCIFer (Allen et al, 2004) and publCIF (Westrip, 2010).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The seven-membered ring is close to being perfectly planar, with no C-C-C-C torsion angle deviating from 0/180 by more than 3 , thus supporting the idea of an aromatic tropylium system. The average of the C-C bond length [1.393 (3) Å ] is close to the values reported for halogen-substituted and unsubstituted tropylium ions (Jandl et al, 2017). However, in contrast to halotropylium ions, the C-C bond lengths of the hydroxytropylium ion show an alternation between the longer C1-C2, C3-C4, C5-C6 and C1-C7 bonds, and the shorter C2-C3, C4-C5 and C6-C7 bonds (Table 2) Computer programs: APEX2 (Bruker, 2013), SAINT (Bruker, 2012), SHELXS97 (Sheldrick, 2008), SHELXL2014 (Sheldrick, 2015), ShelXle (Hü bschle et al, 2011), PLATON (Spek, 2009), Mercury (Macrae et al, 2006), enCIFer (Allen et al, 2004) and publCIF (Westrip, 2010).…”
Section: Resultssupporting
confidence: 82%
“…Hydrogen-bond geometry (Å , ). (Jandl et al, 2017). Such a phenomenon is also possible for hydroxytropylium chloride in solution.…”
Section: Tablementioning
confidence: 90%
See 1 more Smart Citation
“…Thus, we decided to employ bromotropylium bromide 10a (Schemes b,c), which we previously used as halogenating or esterification/amidation reaction promoters. After an extensive optimization study, we found that a stoichiometric amount of 10a could react with the organometallic reagents from aryl halides 3 or react directly with arenes 4 to form intermediates 11 . As the second bromine was able to dissociate off from the newly formed cycloheptatriene ring, 11 could serve as a synthetic equivalent of tropylium salts 1 / 8 , eliminating the need for a lengthy synthetic sequence. Subsequently, the in situ generated 11 was directly subjected to the oxidative ring contraction conditions developed in Table to form the phenylated products (Scheme b,c).…”
mentioning
confidence: 99%